The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00234-020-02490-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure in endovascular stroke treatment of acute basilar artery occlusions—a matched-pair analysis

Abstract: Purpose To determine the radiation exposure in endovascular stroke treatment (EST) of acute basilar artery occlusions (BAO) and compare it with radiation exposure of EST for embolic middle cerebral artery occlusions (MCAO). Methods In this retrospective analysis of an institutional review board−approved prospective stroke database of a comprehensive stroke center, we focused on radiation exposure (as per dose area product in Gy × cm2, median (IQR)), procedure time, and fluoroscopy time (in minutes, median [IQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Several studies have reported on radiation exposure and FT during neurointerventional procedures with modern biplane angiography systems, e.g., mechanical thrombectomy [ 20 , 21 ] and endovascular treatment of intracranial dural arteriovenous fistulae [ 22 , 23 ] or carotid-cavernous fistula [ 24 ]. The aim is to raise awareness of the radiation dose and, in the long term, to optimize the modification of angiography systems and therapeutic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on radiation exposure and FT during neurointerventional procedures with modern biplane angiography systems, e.g., mechanical thrombectomy [ 20 , 21 ] and endovascular treatment of intracranial dural arteriovenous fistulae [ 22 , 23 ] or carotid-cavernous fistula [ 24 ]. The aim is to raise awareness of the radiation dose and, in the long term, to optimize the modification of angiography systems and therapeutic techniques.…”
Section: Discussionmentioning
confidence: 99%